Occupational Exposure to Engineered Nanomaterials: Pathways, Risk Assessment and Regulations - Kuok Ho Daniel Tang (Environmental Research and Planetary Health, 2026)
Occupational exposure to engineered nanomaterials (ENMs) has emerged as a critical concern due to their unique physicochemical properties, which influence their behavior, bioavailability, and toxicity. This review synthesizes current knowledge on occupational exposure pathways, risk assessment strategies, regulatory frameworks, and key challenges associated with ENMs. Occupational exposure occurs predominantly during manufacturing and handling processes, with inhalation identified as the primary route, although dermal and incidental ingestion pathways are also relevant. Exposure characterization remains limited, particularly across the full lifecycle of nano-enabled products, as transformation processes such as dissolution, aggregation, and surface modification can alter exposure profiles. Advances in risk assessment have led to the development of control banding tools, Bayesian networks, weight-of-evidence frameworks, and computational models such as nano-quantitative structure–activity relationship (nano-QSAR) models. Grouping and read-across strategies have also been proposed to address data gaps and reduce testing requirements. However, these approaches remain constrained by insufficient standardized data, variability in dose metrics, and limited regulatory acceptance. Existing lifecycle–based decision support systems offer promising integrated frameworks but remain dependent on data availability and methodological harmonization. This review integrates occupational exposure pathways, emerging risk assessment methodologies, and regulatory developments into a unified lifecycle-oriented perspective. It further offers a critical perspective on how predictive modeling, grouping strategies, and safe-by-design concepts can collectively support preventive rather than reactive nanosafety governance. Despite regulatory progress in the European Union, the United States, and the Asia-Pacific regions, inconsistencies in definitions, data requirements, and nanospecific provisions continue to hinder global harmonization and effective risk management of ENMs.